2020
DOI: 10.3390/s20164585
|View full text |Cite
|
Sign up to set email alerts
|

Activity Energy Expenditure Predicts Clinical Average Levels of Physical Activity in Older Population: Results from Salus in Apulia Study

Abstract: Self-report questionnaires are a valuable method of physical activity measurement in public health research; however, accuracy is often lacking. Resolving the differences between self-reported and objectively measured physical activity is an important surveillance challenge currently facing population health experts. The present work aims at providing the relationship between activity energy expenditure estimated from wrist-worn accelerometers and intensity of self-reported physical activity (InCHIANTI structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Physical activity was assessed through an interviewer‐administered questionnaire [40]. Participants were asked to indicate their average level of physical activity during the past year, with the variable further dichotomized using the cut‐off value <2 [26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity was assessed through an interviewer‐administered questionnaire [40]. Participants were asked to indicate their average level of physical activity during the past year, with the variable further dichotomized using the cut‐off value <2 [26].…”
Section: Methodsmentioning
confidence: 99%
“…The “Salus in Apulia Study” is an ongoing population‐based prospective cohort comprising 2472 individuals aged 65 years old or older and resident in Castellana Grotte, a town near Bari, Puglia, in the Southeast of Italy. The study focuses on lifestyle factors including physical activity [26], diet [27] and other age‐related sensory impairments [28,29] or frailty phenotypes [30]. Salus is a public health initiative funded by the Italian Ministry of Health and Apulia Regional Government, and conducted at our institution, that combines data from two previous populations: a baseline (MICOL3, M3: 2003–2005) and a follow‐up cohort (GreatAGE Study ‐ MICOL4, M4: 2013–2015).…”
Section: Methodsmentioning
confidence: 99%
“…For example, at a data sampling rate of 100 Hz, one accelerometer sensor can provide over 8.6 million samples over a single day. Recently, Borton and coworkers reported that activity energy expenditure derived from wrist-worn wearables can serve as a good predictor of clinical average levels of physical activity in older adults (n = 2472) and thus objectively measure physical activity in a population-based study [20]. Although these vast datasets have rich mobility information, signal processing algorithms to analyze such enormous datasets for extracting essential features relevant to one's mobility are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Motion analysis techniques can provide a more thorough description of 3-dimensional kinematics and offer a noninvasive, dynamic, quantitative alternative to radiographic methods. Motion analysis has been widely used to assess the motor abilities of people with neurological and musculoskeletal impairments[ 11 ]. To our knowledge, there is limited study regarding what biomechanical effect RTC tears have on different motion tasks and muscle activities after surgical treatment of RC tears.…”
Section: Introductionmentioning
confidence: 99%